Healthy and premature aging of monocytes and macrophages - Basu, Syamantak; Ulbricht, Ying; Rossol, Manuela (Frontiers in Immunology, 2025)
Aging is associated with immunosenescence, a decline in immune functions, but also with inflammaging, a chronic, low-grade inflammation, contributing to immunosenescence. Monocytes and macrophages belong to the innate immune system and aging has a profound impact on these cells, leading to functional changes and most importantly, to the secretion of pro-inflammatory cytokines and thereby contributing to inflammaging. Rheumatoid arthritis (RA) is an autoimmune disease and age is an important risk factor for developing RA. RA is associated with the early development of age-related co-morbidities like cardiovascular manifestations and osteoporosis. The immune system of RA patients shows signs of premature aging like age-inappropriate increased production of myeloid cells, accelerated telomeric erosion, and the uncontrolled production of pro-inflammatory cytokines. In this review we discuss the influence of aging on monocytes and macrophages during healthy aging and premature aging in rheumatoid arthritis.